Visual exploration of climate variability in the Philippines - Campano, Wendell Q. (Philippine Statistician, 2013)
In this paper, a data visualization framework for investigating and exploring climate time series data is introduced. This method utilizes the results obtained from performing series of cluster analysis based on a particular multivariate dataset for each defined subset in the time series. The said approach is implemented to the climate data in the Philippines. The data image results obtained from the procedure revealed the expected overall climate pattern in the Philippines as well as some localized segments of climate changes in the time series which deviate from the overall pattern. A wavelet analysis which is a well-established method in analyzing climate data is also done to validate the results shown by the proposed visualization method.